The 1444 Treaty between King Alfonso V of Aragon and Grand Duke Stjepan Vukčić - Peco, Almir (Journal of the Faculty of Philosophy in Sarajevo (History, History of Art, Archeology) / Radovi (Historija, Historija umjetnosti, Arheologija), ISSN 2303-6974 on-line, 2020)
This article discusses a famous agreement between King Alfonso V of Aragon and Naples and the Grand Duke of Bosnia, Stjepan Vukčić Kosača signed on 19 February 1444, as a result of both political and millitary circumstances that had brought, in that particular moment, the local interests of one Bosnian lord and the foreign policy plans and ambitions of the most powerful Mediterranean ruler to the same level. It also offers a new interpretation of this treaty in terms of its practical application, as well as its re-reading and translation, based on a high-resolution facsimile.